A Critical Review of Nidra and Nidranasha – Ayurveda Perspective - Pradhan, Manasi; Das, Arun Kumar; Sahoo, Manoj Kumar; Mishra, Gopinath (International Research Journal of Ayurveda & Yoga, 2023)
Ayuveda is a complete science of life that emphasizes physical and mental wellness and it also includes preventive strategies. Ayurveda incorporates several principles to sustain health and cure disease. The body of a human being is supported by three pillars that are Ahara, Nidra, and Brahmacharya; these three elements are regarded as the Trayopastabmha of life. Nidra is considered as the second pillar of life next to Ahara. If any of these three pillars is disturbed from its usual healthy state, it produces a number of disorders in the human body. Nidranasha is one among them. Nowadays, Nidranasha is a major lifestyle disorder, since people are not following the codes and conducts of life, such as Dinacharya and Ritucharya, and as a consequence, they are suffering from a variety of issues and psychological disorders. In today’s world, numerous sleep disorders are becoming more common as a result of working at night, transmeridian travel, exposure to various electronic devices, and so on. In contrast with modern science, Ayurveda clearly explains Nidra and Nidranasha, and different treatment principles are used to deal with the Nidranasha condition. Because there is no fruitful management in modern science drugs have also created several complications. This article provides a thorough review of the causes, consequences, and management of Nidranasha from an Ayurvedic perspective. In this study, an attempt of critical review on Nidra and Nidranasha is done.